MANAJEMEN LIKUIDITAS SEBAGAI PEDOMAN KERJA DUAL BANKING SYSTEM - Indriatmini Noegroho (BALANCE: Economic, Business, Management and Accounting Journal, 2014)
Liquidity Management in the framework of Dual Banking System. Liquidity management  is a problem that is very complekx in the operational activities of bank.  One of the main triggers  in bank  bankcruptcy,  both in small and large bank, is not because of loss caused by finding, but because of the bank failure to manage liquidity. This article discusses liquidity management in dual banking system. It is found that both SBIS and PUAS can not become the solution to the real problem that was faces by shariah banking an allocating idle money caused by overliquidity.